Seascape Genetics of the Atlantic Spotted Dolphin (Stenella frontalis) Based on Mitochondrial DNA. (28th August 2021) - do Amaral, Karina Bohrer; Barragán-Barrera, Dalia C; Mesa-Gutiérrez, Roosevelt A; Farías-Curtidor, Nohelia; Caballero Gaitán, Susana Josefina; Méndez-Fernandez, Paula; Santos, Marcos C Oliveira; Rinaldi, Caroline; Rinaldi, Renato; Siciliano, Salvatore; Martín, Vidal; Carrillo, Manuel; et al.
Abstract: The Atlantic spotted dolphin ( Stenella frontalis ) is endemic to tropical, subtropical, and warm temperate waters of the Atlantic Ocean. Throughout its distribution, both geographic distance and environmental variation may contribute to population structure of the species. In this study, we follow a seascape genetics approach to investigate population differentiation of Atlantic spotted dolphins based on a large worldwide dataset and the relationship with marine environmental variables. The results revealed that the Atlantic spotted dolphin exhibits population genetic structure across its distribution based on mitochondrial DNA control region (mtDNA-CR) data. Analyses based on the contemporary landscape suggested, at both the individual and population level, that the population genetic structure is consistent with the isolation-by-distance model. However, because geography and environmental matrices were correlated, and because in some, but not all analyses, we found a significant effect for the environment, we cannot rule out the addition contribution of environmental factors in structuring genetic variation. Future analyses based on nuclear data are needed to evaluate whether local processes, such as social structure and some level of philopatry within populations, may be contributing to the associations among genetic structure, geographic, and environmental distance.